Tool of war - Bacigalupi, Paolo (Little, Brown and Company, 2017)
In a future beset with rising seas, corporate government, and constant civil war, a bioengineered half-man/half-beast super-soldier who calls himself Tool breaks his conditioning to overcome his genetically enhanced sense of loyalty to the corporation that created him and seeks revenge against his old masters.